Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

most of the time I know how to find the inverse of a function (make it equal $y$, solve for $x$ and then swap $x$ and $y$), but I have no idea how to do that for this one, so any help would be great: $h(x)=3^x$

From the question:

Solve the equation $h^{-1}(x)=2$

Thanks in advance for any help!

share|cite|improve this question
Logarithms are what you use to invert exponential functions. – J. M. May 2 '12 at 12:54
Wait...the question is to solve $h^{-1}(x)=2$. This is just $x=h(2)=9$, right? – Simon Markett May 2 '12 at 12:59
If you are more interested in a general solution, then $3^x=e^{3ln(x)}$ might help – Simon Markett May 2 '12 at 13:00
As you can see from Simon's comment, the question isn't actually asking you to find the inverse function $h^{-1}$. If that's what you needed to do, you would indeed need logarithms, but as it is, you can treat $h^{-1}$ as a black box without worrying about what function it is, and just write $x=h(h^{-1}(x))=h(2)=3^2=9$. – joriki May 2 '12 at 13:03
up vote 14 down vote accepted

I think both existing answers are sort of missing the point of the exercise. You don't need to know anything about logarithms to do this exercise; all you need are the formal properties of inverse functions. The solution


uses only the specific form of the function $h$ and the general formal properties of inverse functions, not the specific form of $h^{-1}$.

share|cite|improve this answer
That's a great answer! Thanks. – evmunro May 2 '12 at 13:18

You know the process of finding the inverse, so let's go through it step by step.

First, replace $h(x)$ with $y$, $\quad y = 3^x$. Then, switch the $x$ and the $y$, $\quad x = 3^y$. Now, you have to solve for $y$ to find the inverse function. We can't take the $y$-th root of both sides, so in order to solve for $y$, we want to find the exponent that turns 3 into $x$. This is what's called a logarithm. By definition. $y = \log_ax$ if and only if $x = a^y$, that is, $\log_ax$ is the exponent that turns the base $a$ into $x$.

With this in mind, the inverse of $h(x) = 3^x$ would be $h^{-1}(x) = \log_3x$.

To solve the equation $h^{-1}(x) = 2$ we use the above definition.

$$ h^{-1}(x) = 2 \rightarrow \log_3x = 2 \rightarrow x = 3^2 \rightarrow x = 9.$$

share|cite|improve this answer

(I'd like to comment but I don't have that much reputation, sorry...)

You do need logarithms to invert this exponential function! The inverse will be

$$ h^{-1}(x)=\log_3x $$

Therefore, let $2=\log_3x$, we immediately see that $x=3^2=9$.

Additionally: Thanks to @joriki, I believe I need to make things clear. This exercise requires you to establish a better understanding of what an inverse to a function actually means. See joriki's answer!

share|cite|improve this answer
See Simon's comment under the question -- the detour through logarithms is unnecessary. – joriki May 2 '12 at 13:05
I understand that. But I see 'enmunro' is attempting to "find the inverse of a function". I'll edit my answer to detail this. – Dawei May 2 '12 at 13:10
I answered this question 16 mins ago... It's the earliest answer! – Dawei May 2 '12 at 13:19
@DaweiWang: I see, sorry. – Gigili May 2 '12 at 13:21
  1. First replace $h(x)$ with $y$ to get $y=3^x$.
  2. Swap $x, y$ to get $x=3^y$.
  3. Take, for example, $\log_3$ of both sides to get $\log_3x=y\log_33=y.$
  4. Replace $y$ with $h^{-1}(x)$.
  5. $h^{-1}(x)=\log_3(x)$.
share|cite|improve this answer

Denoting f{x) =y, just interchange x and y . It is that simple and also it is done!

$y=3^x $ becomes

$x=3^y , $ or $y_{inv} = \log_3(x) $

Now if $ \log_3(x) =2, x= 3^2 =9. $

You can graph $ f(x) $ and $ f^{-1}(x) $ to check that they indeed intersect on

the line $x=y,$ and nothing more needs to be done.

share|cite|improve this answer

The best way to solve the question is $h^{-1}(x) =2$ then $x=h (2)$

Now solve $h (2) =3^2=9$

So $x=9$

share|cite|improve this answer
Please use MathJax to type your answer. By the way, I don't understand why you are answering this answerd question !! – Nizar Dec 15 '15 at 8:01

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.